Lower-limb endurance training program influences thoracoabdominal motion of patients with COPD? - Danielle Corrêa França; Danielle Soares Rocha Vieira; Bruna da Silva Pinto Pinheiro Vieira; Trícia Guerra e Oliveira; Raquel Rodrigues Britto; Verônica Franco Parreira
INTRODUCTION: Thoracoabdominal-TA asynchrony is an important sign of Chronic Obstructive Pulmonary Disease (COPD). Studies investigating the influence of endurance training on TA asynchrony have not been found. OBJECTIVE: To analyze lower-limb endurance training effects on TA asynchrony in patients with COPD. MATERIALS AND METHODS: Two patients with severe COPD were evaluated in a single-subject design AB (A-baseline for six weeks, B-training on cycle ergometer with intensity of 70% of baseline peak load, for 12 weeks) with repeated measures of variables: phase inspiratory relation (PhRIB), phase expiratory relation (PhREB) and phase angle (PhAng). These variables were assessed by respiratory inductive plethysmography during incremental exercise tests on a cycle ergometer (same load and peak load of each test). Statistical methods included visual analysis, two-standard deviation band test and split middle line test, considering significant p < 0.05. It was considered the results for variables with agreement of at least two analyses. Data are presented as mean ± SD for phases A and B. RESULTS: During phase B, Patient 1 presented significant decrease of PhRIB (22.7 ± 3.4 x 17.0 ± 4.9) and PhAng (16.5 ± 5.1 x 13.2 ± 2.1) for same load and PhREB (16.8 ± 3.1 x 13.3 ± 3.1) and PhAng (23.4 ± 1.7 x 20.1 ± 2.3) at peak load. Patient 2 showed significant decrease of PhRIB for same load and (14.4 ± 3.8 x 13.9 ± 3.9) at peak load (19.1 ± 2.5 x 15.7 ± 2.7). CONCLUSIONS: These results suggest that lower-limb endurance training reduced TA asynchrony in patients with severe COPD. The findings may be related, according to the literature, to the lower ventilatory demand and greater exercise capacity of patients with COPD undergoing endurance training.